Abi Tammam poetry in the old balance of criticism - Salim Al-Hamdany (آداب الرافدين, 1971)
If you search for the flourishing of Arabic literature, then you should only read the poets of the third and fourth centuries of the Hijri. I am only afraid that you find your desire in the poetry of Muslim, Abu Tammam, Al-Buhtari, Al-Mutanabi and others, and if you want to win a fertile critical movement, then read what the critics provoked about the poetry of these people. Only find what you want in what the critics have occupied themselves from the third century AH until this day. I do not see a more fertile, more wonderful, or broader movement than that which was evoked by the poetry of Abi Tammam. The poetry of the Islamic man was occupied just as he occupied his Maghreb and writers and critics were busy studying this poetry and the result of that was a fertile critical movement that had not been witnessed in all eras of literature before. Hence, Abi Tammam's poetry was the subject of a critical movement whose reverberations still reflect the opinions of the critics, from the third century AH until our time. And while the history of Arab literature has preserved, since that era, a huge critical product that was stimulated by the doctrine of Abu Tammam, this does not mean that the movement of criticism around this poetry has been satisfied with what was left of the original monetary heritage, nor does it mean that this wide critical movement has you over everything in the man’s poetry. Of the splendor and creativity of the poet, the poet’s poetry still suggests the most wonderful critical steps among the critics, and the critics still until this age find areas of criticism in which each era can add to what was previously criticized in the spirit of the same era that was on the rest of the images that before it, because the poetry of Abu Tammam hides It contains ideas, meanings and images, which makes his impact extend to the most distant ages, We do not want, here, to search for the history of criticism through the poetry of Abu Tammam, but we want to put the poetry of Abu Tammam in the old balance of currency in order to study the effects that he left in that criticism and to get to know the man’s doctrine through that wide critical movement raised by his poetry. Any modern study of Abu Tammam’s poetry must, in our opinion, take into account two very important points: The first: the culture of Abu Tammam, which relates to philosophy, logic, theology, history, and other things that have been reflected in his poetry, but rather the face of his art in many cases. It helps us in the fairness of the man, which he stirred around him by the critics of his time. And for that, they disputed and devalued his poetry. And the second of them: to understand the spirit of the era in which Abu Tammam lived, to see if his poetry was compatible with the general literary trend that scholars, writers and critics were leading. This point helps us in judging those who criticized his poetry, so they disputed it in his doctrine. Regarding this aspect, it is known that the most critical people in poetry are the narrators and linguists, then the poets, and they were more than they do not relate to modern culture, so they hated hadith on this basis and loved what related to the pillar of Arabic poetry and their influence on what is related to the pillar of philosophy and modern culture. They monitor their poetry to see to what extent these poets were subject to poetry rules and rules The language ? So if a poet deviates from these rules, he becomes in their view out of their way and his poetry becomes an anomaly, indicative of the taste and manner of the times, and in such a case the poet becomes a target of contention, and his poetry is exposed to criticism and insult. In general, all the ancient critics of linguists, grammarians, and narrators did not like the poetry of what came out in the spirit of the times, and they did not accept what was revealed about the general gourmet who uttered and used it, and from here, their opponents felt that Abi Tamam, who undoubtedly had broken the cordon they adopted Mainly to their taste. And he came out with what they were accustomed to from plain and printed poetry, understood without actions of thought or stress of the mind, or its cloudiness to the depths.